Assessing mental health literacy in Jordan: a factor analysis and Rasch analysis study - Al-Qerem, Walid; Jarab, Anan; Khdour, Maher; Eberhardt, Judith; Alasmari, Fawaz; Hammad, Alaa; Zumot, Ruba; Khalil, Sarah (Frontiers in Public Health, 2024)
Background: Mental health literacy (MHL) research in Jordan is sparse and validated MHL measures are lacking. The present study validated a Jordanian version of the Mental Health Literacy Scale (MHLS) and examined Jordanian individuals' MHL. Method: A Google Forms survey was designed, and the link was shared through various Jordanian social media platforms. Factor analysis and Rasch analysis were performed to validate the Jordanian version of the MHLS. Binary logistic regression was performed to assess variables associated with MHL.Results: The Jordanian MHLS was administered to 974 participants (74.4% females; median age 27 years). The mean MHL score of the participants was 71.1% indicating average literacy levels. The factor analysis indicated that 27 items distributed across four factors had the best model fit. The Rasch analysis confirmed item separation reliability and person reliability. The regression showed a correlation between educational attainment, income, marital status and MHL level. These findings emphasize the role of educational attainment in MHL, pointing to the necessity of integrating mental health education into formal curricula to enhance MHL across all societal levels. Stigma and limitedservice availability act as barriers to mental health service and access, which compound the challenge of improving MHL. Targeted educational interventions and policy reforms may help improve MHL, thereby contributing to improving mental health outcomes in Jordan and potentially other similar settings.